Tinjauan Yuridis terhadap Kebijakan Penundaan Pemilihan Kepala Desa di Kabupaten Sampang Berdasarkan Undang-Undang Desa - Wardi; Hwian Christianto (LP3M INSTITUT KH YAZID KARIMULLAH, 2026)
This study aims to analyze the legality of the policy to postpone village head elections in Sampang Regency from a legal perspective, particularly based on Law Number 6 of 2014 concerning Villages. The background of this research is the phenomenon of repeated delays in Pilkades, which has triggered political disputes and legal uncertainty at the village level. This research employs a normative legal method using a statutory approach and a conceptual approach, with qualitative analysis based on library research. The results show that the legal framework governing Pilkades emphasizes the obligation to conduct elections periodically as a manifestation of local democracy and legal certainty. However, the postponement policy implemented in Sampang Regency lacks a clear legal basis and potentially contradicts the principles of legality and legal certainty. Furthermore, prolonged delays have significant legal and democratic implications, including weakened legitimacy of acting village heads and disruption of village autonomy. In conclusion, the postponement of Pilkades in Sampang Regency requires serious evaluation to ensure alignment with the principles of the rule of law and good governance. Therefore, regulatory clarity and strong governmental commitment are necessary to ensure timely implementation of village head elections and to protect the democratic rights of village communities.